Trace elements in magnetite from the pagoni rachi porphyry prospect, NE Greece: Implications for ore genesis and exploration - Mavrogonatos, Constantinos; Voudouris, Panagiotis; Berndt, Jasper; Klemme, Stephan; Zaccarini, Federica; Spry, Paul G.; Melfos, Vasilios; Tarantola, Alexandre; Keith, Manuel; Klemd, Reiner; Haase, Karsten (Minerals, 2019)
Magnetite is a common accessory phase in various types of ore deposits. Its trace element content has proven to have critical implications regarding petrogenesis and as guides in the exploration for ore deposits in general. In this study we use LA-ICP-MS (laser ablation-inductively coupled plasma-mass spectrometry) analyses of trace elements to chemically characterize magnetite from the Pagoni Rachi Cu–Mo–Re–Au porphyry-style prospect, Thrace, northern Greece. Igneous magnetite mostly occurs as euhedral grains, which are commonly replaced by hematite in fresh to propylitic-altered granodiorite porphyry, whereas, hydrothermal magnetite forms narrow veinlets or is disseminated in sodic/potassic-calcic altered (albite + K-feldspar + actinolite + biotite + chlorite) granodiorite porphyry. Magnetite is commonly associated with chalcopyrite and pyrite and locally exhibits martitization. Laser ablation ICP-MS analyses of hydrothermal magnetite yielded elevated concentrations in several trace elements (e.g., V, Pb, W, Mo, Ta, Zn, Cu, and Nb) whereas Ti, Cr, Ni, and Sn display higher concentration in its magmatic counterpart. A noteworthy enrichment in Mo, Pb, and Zn is an unusual feature of hydrothermal magnetite from Pagoni Rachi. High Si, Al, and Ca values in a few analyses of hydrothermal magnetite imply the presence of submicroscopic or nano-inclusions (e.g., chlorite, and titanite). The trace element patterns of the hydrothermal magnetite and especially the decrease in its Ti content reflect an evolution from the magmatic towards the hydrothermal conditions under decreasing temperatures, which is consistent with findings from analogous porphyry-style deposits elsewhere.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Exploration; Hydrothermal; LA-ICP-MS; Magmatic; Magnetite; Porphyry; Trace elements